Efficiency droop in green InGaN/GaN light emitting diodes: Degradation mechanisms and initial characteristics. (September 2020) - Herzog, Alexander; Wagner, Max; Khanh, Tran Quoc
Abstract: This paper describes a comprehensive analysis of the degradation mechanisms of green InGaN based high-power LEDs. The combination of electrical, optical and thermal measurement allows a separation of the degradation mechanisms and their influence on the performance of the devices. The results show that the LEDs have parasitic diodes in their initial state, which influence increases over the aging period. In addition, the recombination coefficients are calculated using the ABC model, which show an increase in the non-radiative recombination coefficients ( A SRH and C ) during stress time. The degradation causes a current-dependent decrease in the external quantum efficiency. Furthermore, a shift of the peak wavelength can be observed, which is due to a change of internal electric fields as well as to the increase of the Shockley-Read-Hall coefficient A SRH . Highlights: Green high-power LEDs indicate a strong degradation for low forward currents. The degradation is due to an increase of the SRH recombination. A shift of the peak wavelength can be observed during degradation.